The innovation dividend of defense R&D - Enrico Moretti; Claudia Steinwender; John Van Reenen (EconPol Forum, 2025)
Research & development (R&D) subsidies, especially defense R&D spending, raise private R&D investment (a crowd-in effect). Public R&D funding increases employment without driving up wages. Supported industries see gains in productivity. International spillovers amplify the impact across countries, underscoring the case for international coordination - particularly within the EU. Direct subsidies outperform tax credits in boosting total R&D.
Keywords: 330